Effectiveness of mindfulness-compassion art therapy on reducing burnout among palliative care professionals - Liew, Shi Hui (2016)
Background: With an aging population, the palliative care sector is facing greater demand. However, as end-of-life care organizations are ill-equipped to support palliative care workers, these professionals are suffering from high burnout levels. Objective: This study examines the efficacy of Mindful-Compassion Art Therapy (MCAT) - a novel intervention - in reducing burnout among Singapore palliative care workers. Methods: 27 participants were enrolled in a single condition – 6 weekly 3-hours sessions of art therapy and mindfulness based therapy group. Self-report assessments - Maslach Burnout Inventory, Five Facet Mindfulness Questionnaire, Self-Compassion Scale–Short Form and WHO Quality of Life Scale 8 - were filled up at pre-intervention and post-intervention periods. The data was analyzed using paired sample t-test and Wilcoxon signed-rank test. In addition, large group discussions during each MCAT sessions were recorded, transcribed and analyzed through directed content analysis. Results: Significant improvements were reported for overall mindfulness score and its sub-domain of non-reactivity. Conclusion: This study showed that MCAT is successful in reducing burnout among palliative care workers through the practice of mindfulness and the process of meaning-making, emotional expression and self-compassion.